Technological capability gap assessment: A study of automotive industry in Thailand - N. Gerdsri (2018)
This paper presents an analytical approach to assess technological capability gaps at an industry level and determine proper strategic areas to support industrial development. A case study of automotive industry in Thailand is presented along with the study on the two strategic scenarios addressing the possibilities for the future development. © 2012 IEEE.